Unlocking the motivations behind vintage luxury desire - Phau, Ian; Akintimehin, O.O.; Shimul, Anwar Sadat; Lee, Sean (2024)
Purpose: Despite the growing popularity of SHVL fashion, there is little empirical focus on the antecedent factors that influence consumers’ intention to purchase and recommend SHVL fashion. Drawing on insights from the stimulus–organism–response framework, this paper aims to investigate the motivational factors influencing the consumers’ attitudes and their intention to purchase and recommend SHVL fashion. Design/methodology/approach: Primary data was gathered from 232 present customers of SHVL fashion products and analysed using the partial least square structural equation modelling. Findings: Research findings show that eco-consciousness, treasure hunting, status consumption and the need for uniqueness were positively linked to intentions to purchase SHVL fashion through the intervening role of attitude. Attitude was positively linked with purchase intentions, which also positively influenced intention to recommend SHVL fashion. Practical implications: The study findings assist brand managers in understanding how they can cater to the diverse needs of SHVL fashion consumers. Originality/value: This research contributes significantly to the SHVL domain by examining core antecedents that motivate consumers’ intention to purchase and recommend SHVL fashion.